Efek profesionalisme, etika profesi, independensi terhadap kinerja auditor dengan pelatihan auditor sebagai variabel moderasi - Benedikta Paifum Ing; Abdul Halim; Lilik Sri Hariani (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2020)
This research aims to test the effect of professionalism, professional ethics, independence to auditor performance with auditor training as a moderation variable on auditors of Public Accounting Firm in Malang. The research method used is quantitative method, with sampling used is puposive sampling. The variables of this research consist of professionalism, professional ethics, independence, auditor training and auditor performance. The results showed partial professionalism, professional ethics, independence, auditor training had an effect on auditor performance and auditor training strengthened the effect of professionalism, professional ethics, independence to auditor performance. It is recommended that further research is expected to add other independent variables that affect auditor performance.